Subchronic administration of creatine produces antidepressant-like effect by modulating hippocampal signaling pathway mediated by FNDC5/BDNF/Akt in mice. (September 2018) - Cunha, Mauricio P.; Pazini, Francis L.; Lieberknecht, Vicente; Rodrigues, Ana Lúcia S.
Abstract: Creatine has been shown to play a significant role in the pathophysiology and treatment of major depressive disorder (MDD) in preclinical and clinical studies. However, the biological mechanisms underlying its antidepressant effect is still not fully elucidated. This study investigated the effect of creatine (p.o.) administered for 21 days in the behavior of mice submitted to tail suspension test (TST), a predictive test of antidepressant activity. Creatine reduced the immobility time in the TST (1–10 mg/kg), without affecting locomotor activity, a finding consistent with an antidepressant profile. Creatine administration increased the ubiquitous creatine kinase (uCK) and creatine kinase brain isoform (CK-B) mRNA in the hippocampus of mice. Taking into account that PGC-1α induces FNDC5/irisin expression mediating BDNF-dependent neuroplasticity, the effect of creatine administration (1 mg/kg, p. o.) on the hippocampal PGC-1α, FNDC5 and BDNF gene expression was investigated. Creatine treatment increased PGC-1α, FNDC5 and BDNF mRNA in the hippocampus as well as BDNF immunocontent. The involvement of BDNF downstream intracellular signaling pathway mediated by Akt, proapoptotic proteins BAX and BAD and antiapoptotic proteins Bcl2 and Bcl-xL was also investigated following creatine treatment. Creatine increased Akt phosphorylation (Ser 473), and Bcl2 mRNA and protein levels, and Bcl-xL mRNA, whereas BAD mRNA was decreased following creatine administration in the hippocampus. Altogether these results indicate that creatine antidepressant-like effect may be dependent on Akt activation and increased expression of the neuroprotective proteins in the hippocampus of mice. The obtained data reinforce the antidepressant property of creatine and highlight the role of these molecular targets in the pathophysiology of MDD. Highlights: Chronic creatine treatment induces antidepressant-like effects. Hippocampal PGC1α and FNDC5 gene expression are upregulated by creatine treatment. Creatine administration increases BDNF immunocontent in the hippocampus. Creatine increases hippocampal Akt phosphorylation. Creatine increases hippocampal mRNA and protein Bcl2.